Finite element analysis of upper crankshaft six stroke engine using CAE software - Muhammad Nasiruddin, Anidin (2009)
This dissertation describes the stress distribution of the upper crankshaft for six stroke engine by using finite element analysis. The finite element analysis is performed by using computer aided engineering (CAE) software. The main objectives of this project are to investigate and analyze the stress distribution of upper piston at the real engine condition during combustion process. The dissertation describes the mesh optimization with using finite element analysis technique to predict the higher stress and critical region on the component. The upper crankshaft is implemented in the six stroke engine of 110 cc Modenas motorcycle. Aluminum 356-T7 is selected as an upper crankshaft material. Despite all the stresses experience by the upper crankshaft does not damage the upper crankshaft due to high tensile strength but the upper crankshaft may fail under fatigue loading. Thus, it is important to determine the critical area of concentrated stress for appropriate modification. With using computer aided design (CAD) which is SOLIDWORK, the structural model of an upper crankshaft is developed. Furthermore, the finite element analysis performed with using MSC PATRAN and MSC NASTRAN. The stress analysis results are significant to improve the component design at the early developing stage. The result can also significantly reduce the cost and time to manufactured the component and the most important to satisfy customer needs.